Association of nutritional status-related indices and chemotherapy-induced adverse events in gastric cancer patients. Issue 1 (December 2016) - Seo, Seung; Kim, Sung-Eun; Kang, Yoon-Koo; Ryoo, Baek-Yeol; Ryu, Min-Hee; Jeong, Jae; Kang, Shin; Yang, Mihi; Lee, Jung; Sung, Mi-Kyung
Abstract Background Malnutrition in gastrectomized patients receiving chemotherapy is associated with the susceptibility to chemotherapy-related adverse events. This study evaluated pre-operative nutritional status-related indices associated with adverse events in post-operation gastric cancer patients receiving chemotherapy. Methods Medical records of 234 gastrectomized patients under adjuvant tegafur/gimeracil/oteracil chemotherapy with extended lymph node dissection were analyzed. Nutritional status assessment included Patient-Generated Subjective Global Assessment (PG-SGA), body weight, body mass index, serum albumin concentration, and Nutrition Risk Index (NRI). Chemotherapy-originated adverse events were determined using Common Terminology Criteria for Adverse Events. Results PG-SGA indicated 59% of the patients were malnourished, and 27.8% of the patients revealed serious malnutrition with PG-SGA score of ≥9. Fifteen % of patients lost ≥10% of the initial body weight, 14.5% of the patients had hypoalbuminemia (<3.5 g/dL), and 66.2% had NRI score less than 97.5 indicating moderate to severe malnutrition. Hematological adverse events were present in 94% (≥grade 1) and 16.2% (≥grade 3). Non-hematological adverse events occurred in 95.7% (≥grade1) and 16.7% (≥grade 3) of the patients. PG-SGA and NRI score was not associated with treatment-induced adverse events. Multivariate analyses indicated that female, low body mass index, and hypoalbuminemia were independent risk factors for grade 3/4 hematological adverse events. Age was an independent risk factor for grade 3/4 non-hematological adverse events. Neutropenia was the most frequently occurring adverse event, and associated risk factors were female, total gastrectomy, and hypoalbuminemia. Conclusions Hypoalbuminemia, not PG-SGA or NRI may predict chemotherapy-induced adverse events in gastrectomized cancer patients.